INDIRECT DAMAGE THAT FOREST FIRES CAUSE TO ROAD INFRASTRUCTURE - Tsekova, Mariana (E-Journal VFU, 2025)
In recent years, forest fires have become an increasingly significant and growing threat to road infrastructure, going beyond direct physical damage. This report analyses the indirect impacts of forest fires, such as environmental changes (erosion, landslides) and critical operational disruptions (road closures, visibility problems, evacuation challenges). It argues that a direct link between the design, construction and maintenance of roads is necessary to build resilient warning and recovery systems.